Six pairs of "characters" in conflict (Journal of Parents and Teachers, 2026)
It analyses how people react to conflicts that arise in the family and at school and emphasises the importance of how to deal with them. It presents six opposing attitudes and how these positions become strategies that prevent the problem from being solved.
Keywords: Conflict, relationships, attitudes, resolution, and coexistence.